Determinants of economic growth in Malaysia / Narina Azni Abdul Ghani and Fadhilah Abdul Jalil - Abdul Ghani, Narina Azni; Abdul Jalil, Fadhilah (Faculty of Business and Management, 2019)
The purpose of this study is to investigate the determinants of economic growth in Malaysia. This study is conducted to investigate the relationship between dependent variable which is Economic Growth in Malaysia and the independent variables which are inflation rate, foreign direct investment, trade openness, unemployment rate and exchange rate. The sources of data were obtained from Data Stream and Word Bank Data. The annual time series for 30 years starting from 1987 until 2017 are used in this study. The data have been collected from various sources. In this study, it is using secondary data and E-views is as one of the methods to measure relationship between the variables studied. This study used Single Linear Regression and Multiple Linear Regression. Based on the result, there is a significant relationship between Foreign Direct Investment, Trade Openness and Exchange Rate towards Economic Growth in Malaysia. Meanwhile, Unemployment Rate and Inflation Rate are considered insignificant towards Economic Growth in Malaysia.